Molecular functionalization of cold-plasma-treated Bombyx mon silk - Piyarat Nimmanpipug (2018)
Bombyx mori silk treated by cold SF6plasma was found to show higher hydrophobic property than the original silk. In order to clarify the chemical changes occurring in this treatment, the changes of functional groups of silk surface were investigated by attenuated total reflection (ATR) infrared spectroscopy, surface charge determination, and quantum mechanical calculation. Infrared spectra of original and plasma-treated silks do not show any change in the frequency regions of amide I, II, and III bands which locate at around 1627, 1513, and 1228 cm-1, respectively. Slight changes were detected for the peak intensities of the bands locating in the frequency region of 1000-1050 cm-1after plasma treatment. This suggests the formation of CF groups in the Bombyx mori silk chain. The zeta potential experiment suggested that the electrostatic charges of the silk surface were not affected by the plasma treatment. In order to investigate the surface state of the plasma treated silk, the density functional calculation was performed for the model compounds with similar chemical structure as that of Bombyx mori silk. In this calculation, a fluorine radical was located at the various positions of the model compound, and the energetically most plausible structures were extracted to show the chemical reaction of CH + F-→ CF + H-. Copyright © 2008 WILEY-VCH Verlag GmbH & Co. KGaA.